Pengaruh Pendapatan Asli Daerah (PAD), Dana Alokasi Umum (Dau), Dan Luas Wilayah Terhadap Alokasi Belanja Modal (Studi Pada Pemerintah Kabupaten/ Kota Se Jawa Tengah Dan DIY) - Saputro, Erwin Dwi; Drs. Atwal Arifin, Drs. Atwal ArifinM.Si., Ak (2016)
The purpose of this research is to know the Native Revenue (PAD), General Allocation Funds (DAU), and an area Against the allocation of capital expenditures. Research method using the method documentation. The sample was done by collecting, recording and calculating the data related to the research took the population of Kabupaten/Kota YOGYAKARTA Central Java and Se in 2012 to 2014. Sampling techniques using the Census Method is a method of taking samples all over the County and cities that exist in Central Java and Yogyakarta.: 1) Multiple Linear regression test, 2) Test t, 3) F Test (test the accuracy of the models) and 4) the coefficient of Determination (R2) Analysis of the results obtained as follows: 1) PAD has an impact on the allocation of capital expenditures, proved the value of sig. of 0.000 of less than 5%, so that the H1 is accepted, 2) DAU had an impact on the allocation of capital expenditure, evidenced by the results of the DAU sig value. of 0.000 of less than 5%, so H2 is received. 3) Locality has no effect on the allocation of capital expenditure, evidenced by the results of GIS value. of 0.063 is greater than 5%, so that the H3 is denied. Key words: Native Revenue (PAD), General Allocation Funds (DAU), Area and capital expenditure Allocation.